The commercialisation of urban elite dwellings in Pompeii: an assessment of the bakeries of Region VI - Hanks, David (2016)
This thesis assesses the often complex commercialisation of elite properties in Pompeii with reference to the bakeries of region VI. Pompeian research has over the years been over theorised with individual approaches failing to transcend multidepartmental boundaries. This paper selects five elite domestic/ previously domestic properties in region VI from Pompeii, for their association with the baking industry. It assesses the architectural changes of the properties and material culture to highlight the potential motivational factors behind the addition of bakeries within such residences. The results from this analysis highlight the significant involvement of the social elite within the baking industry. While the evidence suggests that the industry was largely overseen by a workforce that transcended the social spectrum of the city. However, the elites gained more through the addition of bakeries within their properties than the potential loss of social status, from which the literary sources may lead us to believe. This paper also reassesses the early work of Mauri (1942) with his now largely discredited argument that the social elite had abandoned the city following the earthquake of A.D 62. Instead this paper suggests that the earthquake did not serve as a coup de grace of the social elite, but an opportunity to revitalise their urban property portfolio, manage assets and consolidate the growth of their personal finance in a select number of properties.